Detection of Audio-based Emergency Situations using Perception Sensor Network - Quang Nguyen; Yun, Sang-Seok; Choi, JongSuk (2016 13TH INTERNATIONAL CONFERENCE ON UBIQUITOUS ROBOTS AND AMBIENT INTELLIGENCE (URAI), 2016)
This paper presents a perception sensor network (PSN) for detect audio-based emergency situations such as human scream. The PSN consists of multiple units, each has a Kinect and a pan-tilt-zoom camera. Audio signals, which are acquired by the Kinect microphone array, are used in sound source classification and sound source localization. In order to work in multi-person scenarios, we propose an audio-visual fusion method to detect a single speaking person among multiple ones. The PSN system was demonstrated in a scenario having four persons, where the system is able to detect and localize the screaming person and send a robot to that location to check his/her condition.